The Influence of Advertising and Product Bundling on Smartphone Purchase Intentions at Art Celluler: The Mediating Role of Customer Attitude - Arohman, Afif; Wibawanto, Sigit ` (Journal of Educational Management Research, 2025)
This study explores how advertising and product bundling influence smartphone purchase intention at Art Celluler, both directly and indirectly through customer attitude. Using a quantitative approach and purposive sampling, data were gathered from 100 respondents via offline questionnaires. Analysis was conducted with Structural Equation Modeling  using the Partial Least Square method in SmartPLS 4. Results reveal that advertising significantly drives purchase intention directly, but does not shape customer attitudes. In contrast, product bundling has a strong impact on both customer attitude and purchase intention. Interestingly, customer attitude itself does not significantly influence purchase intention, and the mediating role of attitude was found to be insignificant for both advertising and bundling. These findings highlight the strategic value of direct advertising in prompting immediate consumer action, while product bundling emerges as a dual-force strategy—enhancing perception and driving sales. For marketing managers, this suggests prioritizing clear, compelling promotions and bundling offers rather than relying solely on attitude-shaping campaigns. Firms in competitive retail environments can optimize their promotional mix by focusing on tangible value propositions that directly convert interest into action.